Spinel-phase Li4Mn5O12-coated high-nickel positive electrode material as well as preparation method and application thereof

By covering spinel phase Li4Mn5O12 nanoparticles on the surface of the high-nickel positive electrode material, the challenges of the high-nickel positive electrode material in terms of cycle stability and rate performance are solved, and the performance improvement of the material and the battery life are achieved.

CN119447241AInactive Publication Date: 2025-02-14SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411576473.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

High-nickel cathode materials have great challenges in cycle stability and rate performance, resulting in limited application in lithium-ion batteries.

Method used

By covering spinel phase Li4Mn5O12 nanoparticles on the surface of high nickel positive electrode material, a cladding layer with a thickness of 5~30 nm is formed, and the stability of spinel and three-dimensional lithium ion diffusion channels are used to improve the circulation stability of the material and Rate performance.

Benefits of technology

It effectively improves the cycling stability and rate performance of high-nickel cathode materials, extends the battery life, and increases the operating voltage to 4.6 V, and the discharge specific capacity at a current density of 0.1 C is greater than 235 mAh g-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447241A_ABST
    Figure CN119447241A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery positive electrode materials, and particularly relates to a spinel phase Li4Mn5O12 coated high-nickel positive electrode material as well as a preparation method and application thereof. A substrate of the material is a high-nickel positive electrode material, a coating layer is arranged on the surface of the substrate, and the coating layer is spinel-phase Li4Mn5O12 nanoparticles; the spinel phase Li < 4 > Mn < 5 > O < 12 > accounts for 1%-3% of the high-nickel positive electrode material by mass; the chemical general formula of the high-nickel positive electrode material is LiNi < 1-x-y > Co < x > Mn < y > O < 2 >, wherein (1-x-y) < lt > is greater than or equal to 0.8; 1, 0lt; xlt; 0, 0, 0, 0; yt; Yt; and 0.2 part. The spinel with relatively high lattice matching degree with the high-nickel positive electrode material can avoid a coating layer fracture phenomenon caused by volume expansion of the coating layer; a spinel three-dimensional lithium ion diffusion channel is adopted, so that the de-intercalation rate of lithium ions is increased, and the rate capability of the high-nickel positive electrode material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery positive electrode materials, and specifically relates to a spinel phase Li4Mn5O 12 Coated high-nickel positive electrode material, preparation method and application thereof. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in electric vehicles, consumer electronics, energy storage systems and other fields due to their high energy density, long cycle life and stability. However, with the development of society and science and technology, the demand for higher performance batteries has increased, and the limitations of traditional positive electrode materials in terms of energy density, cycle stability and safety have gradually emerged. In order to solve these problems, the modification of positive electrode materials has become one of the key means to improve the overall performance of lithium-ion batteries. By optimizing the structure, modifying the surface, doping and developing new materials of positive electrode materials, the electrochemical properties of the materials can be effectively improved, their cycle stability can be enhanced and the battery life can be extended.

[0003] Environmentally friendly rechargeable lithium-ion batteries play an important role in the new energy industry. With the development of society and science and technology, hybrid vehicles and electric vehicles have increasing requirements for the energy density of lithium-ion batteries. Commercial cathode materials such as LiCoO2 and LiFePO4 are difficult to meet the high energy density requirements of lithium-ion batteries due to their low reversible capacity and low operating voltage. 1-x-y Co x Mn y O2, has a higher theoretical specific capacity (>250mAh g -1 ) and a wider voltage range (2.7 to 4.3 V vs. Li + / Li), is expected to become the cathode material for the next generation of high energy density lithium-ion batteries. However, some inherent defects of this material currently seriously hinder its commercial application: (1) In the charged state, the highly active Ni 4+ It is easy to have chemical side reactions with the electrolyte, causing the electrolyte to decompose and produce gas products and CEI phase. At the same time, the surface of the high-nickel positive electrode material undergoes chemical degradation and transforms into an electrochemically inert NiO rock salt phase, which greatly hinders the Li + At the same time, the lattice oxygen on the surface of the material is released in the charged state, which can easily trigger thermal runaway in the presence of electrolyte, causing safety hazards; (2) Mechanical failure of the cathode material will aggravate the surface chemical degradation of the high nickel cathode material. During the cycle, the anisotropic lattice volume change will produce intergranular microcracks, which will promote the continuous penetration of the electrolyte into the secondary particles along the grain boundaries, aggravating the chemical side reactions of the internal primary particles. Microcracks and surface structural degradation significantly increase the electrode impedance, hindering the Li + diffusion and electron transport, leading to capacity fading.

[0004] Surface modification has been proven to effectively improve the cycle performance of high-nickel cathode materials. Through surface modification, a protective interface can be formed on the surface of high-nickel cathode materials to reduce structural damage caused by electrolyte corrosion, thereby achieving the purpose of improving the cycle stability of high-nickel cathode materials. However, the commonly used modification methods are difficult to solve the cycle stability and rate problems of high-nickel cathode materials. Summary of the invention

[0005] The present invention aims to provide a spinel phase Li4Mn5O 12 The coated high-nickel positive electrode material and its preparation method and application solve the problems of poor cycle stability and low rate performance of high-nickel positive electrode materials.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a spinel phase Li4Mn5O 12 The coated high nickel positive electrode material has a substrate of high nickel positive electrode material and a coating layer on the surface of the substrate, and the coating layer is spinel phase Li4Mn5O 12 Nanoparticles; Among them, spinel Li4Mn5O 12 The mass ratio is 1% to 3% of the high nickel positive electrode material; The general chemical formula of high nickel cathode material is: LiNi 1-x-y Co x Mn y O2, where 0.8≤(1-xy)<1, 0 <x<0.2,0<y<0.2。

[0007] Furthermore, the coating layer has a thickness of 5 to 30 nm.

[0008] The present invention also discloses the spinel phase Li4Mn5O 12 The method for preparing the coated high-nickel positive electrode material comprises the following steps: Ultrasonic dispersion of high nickel cathode material in anhydrous ethanol solution to form a black suspension; Soluble metal manganese salt and hydroxyl-containing template were dissolved in anhydrous ethanol to form a colorless transparent solution as Li4Mn5O 12 Precursor of Add the colorless transparent solution into the suspension, and continue to heat at a constant temperature for 4 to 8 hours to obtain a uniform mixed solution; The mixed solution is centrifuged to collect the solid phase product; The solid phase product was heat treated in an oxygen atmosphere and naturally cooled to obtain the spinel phase Li4Mn5O 12 Coated high nickel positive electrode material.

[0009] Furthermore, the metal manganese salt is manganese nitrate or manganese acetate.

[0010] Furthermore, the template agent is hexamethylenetetramine, polyvinyl pyrrolidone or hexadecyltrimethylammonium bromide.

[0011] Furthermore, in the constant temperature stirring heating, the heating temperature is 60-100°C.

[0012] Furthermore, the heat treatment temperature is 700-800°C and the time is 2-6 hours.

[0013] The present invention also discloses a spinel phase Li4Mn5O 12 Application of coated high nickel cathode materials in the preparation of lithium ion batteries.

[0014] Furthermore, the operating voltage of the lithium-ion battery can be increased to 4.6 V, and the discharge capacity at a current density of 0.1 C is greater than 235 mAh g -1 .

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a spinel phase Li4Mn5O 12 Coated high nickel cathode material, spinel Li4Mn5O 12 The lattice stability is high. When coated on the surface of high-nickel positive electrode materials, it can not only reduce the corrosion of the electrolyte on the active material, inhibit the precipitation of lattice oxygen of high-nickel positive electrode materials, and enhance the cycle stability of high-nickel rich positive electrode materials; spinel with a high lattice matching degree with high-nickel positive electrode materials can avoid the coating layer from breaking due to volume expansion; spinel three-dimensional lithium ion diffusion channel increases the lithium ion deintercalation rate and enhances the rate performance of high-nickel positive electrode materials.

[0016] Furthermore, the spinel phase Li4Mn5O 12 The thickness of the coating layer is 5~30 nm. When the coating layer is too thin, it is difficult to effectively block the contact between the positive electrode material and the electrolyte, and certain side reactions will still occur, affecting the cycle stability of the material; when the coating layer is too thick, it will hinder the transmission path of lithium ions, increase resistance, and reduce the conductivity and rate performance of the battery.

[0017] The present invention aims to provide a spinel phase Li4Mn5O 12 The preparation method of the coated high-nickel positive electrode material adopts a simple wet chemical method, using a template agent to continuously release hydroxyl groups after heating, which combine with metal manganese ions to form a uniform and Li-ion-containing layer on the surface of the high-nickel positive electrode material. + The Mn(OH)2 nanoshell of the capture layer is converted into spinel phase Li4Mn5O at a high temperature of 700-800 °C and a sintering time of 2-6 h. 12 Coating. If the temperature during the preparation process is lower than 700°C, the material will have poor crystallinity and low capacity; if the temperature is higher than 800°C, lithium will volatilize, reducing the material performance. Spinel Li4Mn5O 12 The coating has good ionic and electronic conductivity, which is beneficial to improve the Li + Migration kinetics, thereby improving the rate performance of high nickel materials. 12 The coating thickness can effectively inhibit electrolyte corrosion and interfacial side reactions, thereby improving the electrochemical stability of the interface between the high-nickel cathode and the electrolyte. 12 The coated high-nickel cathode material can increase the working cut-off voltage from the conventional 4.3 V to 4.6 V, and the discharge capacity at a current density of 0.1 C is greater than 235 mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Li4Mn5O prepared in Example 1 12 X-ray diffraction patterns of the coated high-nickel cathode material (LMO@NCM) and the sample prepared in Example 2.

[0019] Figure 2 This is a transmission electron microscopy image of LMO@NCM prepared in Example 1.

[0020] Figure 3 Comparison of the cycling performance of LMO@NCM prepared in Example 1 and uncoated NCM under 1C test conditions.

[0021] Figure 4 This is the rate performance diagram of LMO@NCM prepared in Example 1 and Example 2. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the present invention clearer, the following is further described in detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, not all embodiments. Based on the drawings and embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0023] The present invention discloses a spinel phase Li4Mn5O 12 The coated high nickel positive electrode material has a substrate of high nickel positive electrode material and a coating layer on the surface of the substrate, and the coating layer is spinel phase Li4Mn5O 12 Nanoparticles; Among them, the spinel phase Li4Mn5O 12 The mass ratio is 1% to 3% of the high nickel positive electrode material; The general chemical formula of high nickel cathode material is: LiNi 1-x-y Co x Mn y O2, where 0.8≤(1-xy)<1, 0 <x<0.2,0<y<0.2。

[0024] Spinel phase Li4Mn5O 12 The method for preparing the coated high-nickel positive electrode material comprises the following steps: Ultrasonic dispersion of high nickel cathode material in anhydrous ethanol solution to form a black suspension; Soluble metal manganese salt and hydroxyl-containing template were dissolved in anhydrous ethanol to form a colorless transparent solution as Li4Mn5O 12 Precursor of Add the colorless transparent solution into the suspension, and continue to heat at a constant temperature for 4 to 8 hours to obtain a uniform mixed solution; The mixed solution is centrifuged to collect the solid phase product; The solid phase product was heat treated in an oxygen atmosphere and naturally cooled to obtain the spinel phase Li4Mn5O 12 Coated high nickel positive electrode material.

[0025] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0026] Example 1 (1) 10 g LiNi 0.8 Co 0.1 Mn 0.1 O2 was ultrasonically dispersed in 300 mL of anhydrous ethanol solution to form a black suspension.

[0027] (2) Spinel Phase: 1.6 g of soluble manganese acetate and 1.67 g of hexamethylenetetramine were dissolved in anhydrous ethanol at a mass ratio of 1 wt% to form a colorless transparent solution.

[0028] (3) A colorless and transparent solution containing a metal salt and a template is added dropwise into a suspension containing a high-nickel cathode material, and the mixture is heated in an oil bath with constant stirring for 4 h at a temperature of 60 °C to obtain a uniform mixed solution.

[0029] (4) The mixed solution obtained above was centrifuged, and the collected black powder was heat-treated in an oxygen atmosphere at a temperature of 750 °C for 2 h. After natural cooling, spinel Li4Mn5O 12 High nickel cathode material after oxide surface modification, labeled as 1%-LMO@NCM.

[0030] The spinel Li4Mn5O prepared in this example 12 The X-ray diffraction pattern (XRD) of the coated high nickel cathode material is as follows: Figure 1 shown. Figure 1 The XRD diffraction peaks in LiNi 0.8 Co 0.1 Mn 0.1 The O2 crystal phase matches well, indicating that the coating process will not destroy the crystal structure of the high-nickel positive electrode material.

[0031] The spinel Li4Mn5O prepared in this example 12 The transmission electron microscope (TEM) image of the coated high nickel cathode material is as follows: Figure 2 shown. Figure 2 The lattice fringe spacing of the surface phase is 0.167nm, 0.247nm, and 0.288nm, corresponding to the spinel phase Li4Mn5O 12 (422), (331), (2-20) crystal planes; the lattice fringe spacing of the internal crystal is 0.236nm, 0.245nm, corresponding to LiNi 0.8 Co 0.1 Mn 0.1 O2 phase (101) and (006) crystal planes. The results show that the spinel phase Li4Mn5O 12 Successfully coated on LiNi 0.8 Co 0.1 Mn 0.1 O2 surface, the coating thickness is about 18nm.

[0032] Battery performance test: The obtained high nickel cathode material, polyvinylidene fluoride as a binder, and carbon black as a conductive agent were dispersed in an organic solvent N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and then evenly coated on the current collector aluminum foil, rolled to the required compaction density after drying, and vacuum dried at 80 °C for 12 h. The pole piece was cut into a disc with a diameter of 12 mm, and a metal lithium sheet was used as the counter electrode. A Celgard 2400 model diaphragm was used, and a mixed solution of 1 mol / L LiPF6 dissolved in EC and DMC (EC / DMC volume ratio 1:1) was used as the electrolyte. CR2025 button cells were assembled in an argon glove box.

[0033] The prepared lithium-ion battery was subjected to cycle performance and rate performance tests. Figure 3 As shown in Figure 2, the operating cut-off voltage can be increased from the conventional 4.3 V to 4.6 V, and the discharge capacity at a current density of 0.1 C is greater than 235 mAhg -1 After 150 cycles at 1 C current density, the capacity retention rate was 84.5%.

[0034] Rate performance Figure 4 As shown in the figure, the discharge capacity of the coated samples at various rates is significantly improved compared with the uncoated samples (NCM).

[0035] Example 2 (1) 10 g LiNi 0.8 Co 0.1 Mn 0.1 O2 was ultrasonically dispersed in anhydrous ethanol solution to form a black suspension.

[0036] (2) Spinel Phase Soluble manganese acetate (3.2 g) and hexamethylenetetramine (3.34 g) were dissolved in anhydrous ethanol at a mass ratio of 2 wt% to form a colorless transparent solution.

[0037] (3) A colorless and transparent solution containing a metal salt and a template is added dropwise into a suspension containing a high-nickel cathode material, and heated in an oil bath at a constant temperature of 80 °C for 8 h with continuous stirring.

[0038] (4) The obtained solution was centrifuged, and the collected black powder was heat treated in an oxygen atmosphere at a temperature of 750 °C for 2 h. After natural cooling, spinel Li4Mn5O 12 The coated high-nickel cathode material is labeled as 2%-LMO@NCM.

[0039] The spinel Li4Mn5O prepared in this example 12 The X-ray diffraction pattern (XRD) of the coated high nickel cathode material is as follows: Figure 1 shown. Figure 1 The XRD diffraction peaks in LiNi 0.8 Co 0.1 Mn 0.1 The O2 crystal phase matches well, indicating that the coating process will not destroy the crystal structure of the high-nickel positive electrode material.

[0040] Battery performance test: The obtained high nickel cathode material, polyvinylidene fluoride as a binder, and carbon black as a conductive agent were dispersed in an organic solvent N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1, and then evenly coated on the current collector aluminum foil, rolled to the required compaction density after drying, and vacuum dried at 80 °C for 12 h. The pole piece was cut into a disc with a diameter of 12 mm, and a metal lithium sheet was used as the counter electrode. A Celgard 2400 model diaphragm was used, and a mixed solution of 1 mol / L LiPF6 dissolved in EC and DMC (EC / DMC volume ratio 1:1) was used as the electrolyte. CR2025 button cells were assembled in an argon glove box.

[0041] Rate performance Figure 4 As shown in the figure, the discharge capacity of the coated samples at various rates is significantly improved compared with the uncoated samples (NCM).

[0042] Example 3 (1) Add appropriate amount of LiNi 0.9 Co 0.05 Mn 0.05 O2 was ultrasonically dispersed in anhydrous ethanol solution to form a black suspension.

[0043] (2) Spinel oxide: Soluble manganese acetate and polyvinyl pyrrolidone are dissolved in anhydrous ethanol at a mass ratio of 3 wt% to form a colorless transparent solution.

[0044] (3) A colorless transparent solution containing a metal salt and a template is added dropwise into a suspension containing a high-nickel cathode material, and heated in an oil bath with constant stirring for 4 h at a temperature of 100 °C.

[0045] (4) The obtained solution was centrifuged, and the collected black powder was heat treated in an oxygen atmosphere at 800 °C for 3 h. After natural cooling, spinel Li4Mn5O 12 Coated high nickel positive electrode material.

[0046] Example 4 (1) Add appropriate amount of LiNi 0.9 Co 0.05 Mn 0.05 O2 was ultrasonically dispersed in anhydrous ethanol solution to form a black suspension.

[0047] (2) Spinel oxide: Soluble manganese acetate and cetyltrimethylammonium bromide are dissolved in anhydrous ethanol at a mass ratio of 1 wt% to form a colorless transparent solution.

[0048] (3) A colorless transparent solution containing a metal salt and a template is added dropwise into a suspension containing a high-nickel cathode material, and heated in an oil bath at a constant temperature of 80 °C for 5 h with continuous stirring.

[0049] (4) The obtained solution was centrifuged, and the collected black powder was heat treated in an oxygen atmosphere at a temperature of 720 °C for 4 h. After natural cooling, spinel Li4Mn5O 12 Coated high nickel positive electrode material.

[0050] The Li4Mn5O 12 The invention discloses a method for preparing a uniformly coated high-nickel positive electrode material, wherein a uniform hydroxide coating layer is in situ generated on the surface of the high-nickel positive electrode material by a wet chemical method, and an ion rearrangement is caused by a phase transformation induced by residual lithium on the surface during high-temperature sintering to form a spinel phase Li4Mn5O with a three-dimensional ion channel. 12 The coating layer helps to improve the kinetics of lithium ion migration, thereby improving the rate performance of the battery. The coating layer can optimize the interface compatibility, reduce interface defects, effectively inhibit the side reactions between the high-nickel positive electrode material and the electrolyte, reduce surface oxygen evolution, corrosion and structural degradation, and improve the battery cycle stability of the material. This strategy can improve the structural stability of the high-nickel positive electrode, and can also improve the rate performance, working voltage and cycle stability of the positive electrode.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A spinel phase Li4Mn5O 12 The coated high nickel positive electrode material is characterized in that The substrate is a high-nickel positive electrode material, and the substrate surface has a coating layer, which is a spinel phase Li4Mn5O 12 Nanoparticles; Among them, the spinel phase Li4Mn5O 12 The mass ratio is 1% to 3% of the high nickel positive electrode material; The general chemical formula of high nickel cathode material is: LiNi 1-x-y Co x Mn y O2, where 0.8≤(1-xy)<1, 0 <x<0.2,0<y<0.2。 2. The spinel phase Li4Mn5O according to claim 1 12 The coated high nickel positive electrode material is characterized in that The thickness of the coating layer is 5-30 nm.

3. The spinel phase Li4Mn5O according to claim 1 or 2 12 The method for preparing the coated high-nickel positive electrode material is characterized in that: The following steps are involved: Ultrasonic dispersion of high nickel cathode material in anhydrous ethanol solution to form a black suspension; Soluble metal manganese salt and hydroxyl-containing template were dissolved in anhydrous ethanol to form a colorless transparent solution as Li4Mn5O 12 Precursor of Add the colorless transparent solution into the suspension, and continue to heat at a constant temperature for 4 to 8 hours to obtain a uniform mixed solution; The mixed solution is centrifuged to collect the solid phase product; The solid phase product was heat treated in an oxygen atmosphere and naturally cooled to obtain the spinel phase Li4Mn5O 12 Coated high nickel positive electrode material.

4. The spinel phase Li4Mn5O according to claim 3 12 The method for preparing the coated high-nickel positive electrode material is characterized in that: The metal manganese salt is manganese nitrate or manganese acetate.

5. The spinel phase Li4Mn5O according to claim 3 12 The method for preparing the coated high-nickel positive electrode material is characterized in that: The template agent is hexamethylenetetramine, polyvinyl pyrrolidone or hexadecyltrimethylammonium bromide.

6. The spinel phase Li4Mn5O according to claim 3 12 The coated high-nickel positive electrode material and the preparation method thereof are characterized in that: In the constant temperature stirring heating, the heating temperature is 60-100°C.

7. The spinel phase Li4Mn5O according to claim 3 12 The coated high-nickel positive electrode material and the preparation method thereof are characterized in that: The heat treatment temperature is 700-800°C and the time is 2-6 hours.

8. A spinel phase Li4Mn5O according to any one of claims 1 to 7 12 Application of coated high nickel cathode materials in the preparation of lithium ion batteries.

9. The spinel phase Li4Mn5O according to claim 8 12 The application of the coated high nickel positive electrode material in the preparation of lithium ion batteries is characterized in that: The operating voltage of the lithium-ion battery can be increased to 4.6 V, and the discharge capacity at a current density of 0.1 C is greater than 235 mAh g -1 .

Citation Information

Patent Citations

  • Method for synthesizing Li4Mn5O12 sub-micrometer rod

    CN101764224A

  • Spinel oxide coated lithium-rich manganese-based positive electrode material

    CN113571679A

Cited By

  • Composite positive electrode material capable of being used for solid-state battery and preparation method and application of composite positive electrode material

    CN120565627A

  • Preparation method and application of in-situ polymerization coated spinel MgMn2O4 positive electrode material

    CN120698507A